2022
DOI: 10.1002/jobm.202200513
|View full text |Cite
|
Sign up to set email alerts
|

Effect of biosynthesized selenium nanoparticles using Nepeta extract against multidrug‐resistant Pseudomonas aeruginosa and Acinetobacter baumannii

Abstract: The problems of drug resistance in bacteria have become one of the daily challenges of the clinical treatment of patients, which inevitably forces us to use agents other than common antibiotics. Among these, we can take help from different properties and applications of nanoparticles (NPs). In this work, we evaluate the antibacterial activity of biosynthesized selenium nanoparticles (SeNPs) against standard strains of multidrug‐resistant Pseudomonas aeruginosa and Acinetobacter baumannii. The production of bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 58 publications
0
9
0
Order By: Relevance
“…In the current study, SeNPs showed antibacterial activity against all tested CRABs, with MICs lower than 0.07 mg/mL for two thirds of the isolates. Accordingly, previously published articles strongly suggested the wide-spectrum antibacterial activity of SeNPs against a variety of microbes, including Gram-negative bacteria, such as E. coli , P. aeruginosa , and A. baumannii [ 54 , 55 , 56 ]. However, to the best of our knowledge, this is the first study evaluating the antibiofilm efficacy of SeNPs against CRABs with confirmed biofilm-producing capacity.…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, SeNPs showed antibacterial activity against all tested CRABs, with MICs lower than 0.07 mg/mL for two thirds of the isolates. Accordingly, previously published articles strongly suggested the wide-spectrum antibacterial activity of SeNPs against a variety of microbes, including Gram-negative bacteria, such as E. coli , P. aeruginosa , and A. baumannii [ 54 , 55 , 56 ]. However, to the best of our knowledge, this is the first study evaluating the antibiofilm efficacy of SeNPs against CRABs with confirmed biofilm-producing capacity.…”
Section: Discussionmentioning
confidence: 99%
“…The use of plant extracts (Urtica dioica, Ricinus communis, Artemisia annua, Nepeta sp., etc.) during synthesis also enhances the antibacterial and antifungal effects of SeNPs [117,148,150,175]. The addition of SeNPs to titanium oxide nanotubes enhances the antibacterial properties of the latter [176][177][178].…”
Section: Influence Of Selenium Nanoparticle Synthesis Methods On the ...mentioning
confidence: 98%
“…This approach is also based on the reduction of selenium-containing precursors to Se 0 . The essential difference between the first and the second type is that biogenic synthesis uses cellular structures [115,131,[146][147][148][149] and bioorganic synthesis uses noncellular extracts of plant and microbial origin to synthesize nanoparticles [117,132,[150][151][152][153]. In this case, reducing agents are usually secondary metabolites, such as flavonoids, thiamine and capsaicin, as well as other agents containing amino groups, extracted from various plants: Spirulina platensis, Azadirachta indica, Trigonella foenum-graecum, Allium sativum, etc.…”
Section: Synthesis Methods Of Selenium Nanoparticlesmentioning
confidence: 99%
See 2 more Smart Citations